The Effect of Tri Guna in Educational Psychology - Ni Wayan Ramini Santika (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
In this life, there are differences in human behavior, so that they run according to their respective svadharma. A person's current position will be influenced by the nature he was born with, namely (sattvam) goodness, (rajas) lust, and (tamas) ignorance. Thus all thoughts, words, and actions of each individual is a reflection of one's behavior in society, then the influence of the nature of sattvam, rajas and tamas nature will have an impact on the level of belief of each individual. Opportunities in this life, which are influenced by the tri guna, even though they have different levels of understanding of beliefs, all of these can be used as basic capital to change all behaviors for the better. This can be realized when making a choice in acting or doing, if always by prioritizing the nature of sattvam. The Rajas and Tamas properties are used in the right circumstances and conditions. Educational Psychology can play a role in creating a number of effective ways of teaching. Educational Psychology emphasizes the teaching and learning process and the factors that influence it, both internally and externally.